Persuasion, reflection, judgment : Ancillae Vitae - Gasché, Rodolphe (Bloomington : Indiana University Press, 2017)
As one of the most respected voices of Continental philosophy today, Rodolphe GaschE pulls together Aristotle's conception of rhetoric, Martin Heidegger's debate with theory, and Hannah Arendt's conception of judgment in a single work on the centrality of these themes as fundamental to human flourishing in public and political life. GaschE's readings address the distinctively human space of the public square and the actions that occur there, and his valorization of persuasion, reflection, and judgment reveals new insight into how the philosophical tradition distinguishes thinking from other faculties of the human mind.
Persuasion (Aristotle) -- A truth resembling truth -- Probability or necessity -- Logos, topos, stoikheion -- Reflection (Heidegger) -- Breaking with the primacy of the theoretical -- The genesis of the theoretical -- Beyond theory: theoria, or watching over what is still to come -- Judgment (Arendt) -- The space of appearance -- The wind of thought -- A sense of the world.
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Aristotle; Heidegger, Martin, -- 1889-1976.; Arendt, Hannah, -- 1906-1975.; Arendt, Hannah, -- 1906-1975; Aristotle; Heidegger, Martin, -- 1889-1976; Phenomenology; Persuasion (Rhetoric); Judgment; Judgment; Phénoménologie.; Jugement; phenomenology; PHILOSOPHY -- Metaphysics; PHILOSOPHY -- Movements -- Phenomenology; Judgment; Persuasion (Rhetoric); Phenomenology